Waist circumference as a mediator of biological maturation effect on the motor coordination in children - Leonardo G.O. Luz; André Seabra; Cristina Padez; João P. Duarte; Ricardo Rebelo-Gonçalves; João Valente-; Tatiana D.D. Luz; Bruno C.M. Carmo; Manuel Coelho-
Abstract Objective: The present study aimed to: 1) examine the association of biological maturation effect on performance at a motor coordination battery and 2) to assess whether the association between biological maturation and scores obtained in motor coordination tests is mediated by some anthropometric measurement. Methods: The convenience sample consisted of 73 male children aged 8 years old. Anthropometric data considered the height, body mass, sitting height, waist circumference, body mass index, fat mass and fat-free mass estimates. Biological maturation was assessed by the percentage of the predicted mature stature. Motor coordination was tested by the Körperkoordinationstest für Kinder. A partial correlation between anthropometric measurements, z-score of maturation and the motor coordination tests were performed, controlling for chronological age. Finally, causal mediation analysis was performed. Results: Height, body mass, waist circumference and fat mass showed a slight to moderate inverse correlation with motor coordination. Biological maturation was significantly associated with the balance test with backward walking (r=-0.34). Total mediation of the waist circumference was identified in the association between biological maturation and balance test with backward walking (77%). Conclusions: We identified an association between biological maturation and KTK test performance in male children and also verified that there is mediation of waist circumference. It is recommended that studies be carried out with female individuals and at other age ranges.